Limits of Criminal Liability in Public Auctions by Indonesian Officials - Mhd. Ansor Lubis; Aras Firdaus; Ica Karina; Muslim Harahap; H. Abdul Lawali Hasibuan; Gerald Elisa Munthe (Indonesian Journal of Law and Policy Studies, 2025)
The implementation of auctions by public officials is part of government action that has administrative and criminal legal implications. In practice, legal issues often arise that lead to criminal liability for auction officials, especially when procedural deviations or abuse of authority occur. This study aims to analyze the limits of criminal liability in the implementation of auctions by public officials based on the Indonesian constitutional system. The research method used is normative legal research with a statutory and conceptual approach. The results show that criminal liability for public officials in the implementation of auctions must be clearly demarcated between administrative errors and criminal acts, while still paying attention to the principle of legality, general principles of good governance, and the doctrine of abuse of authority. Therefore, it is necessary to strengthen regulations and harmonize state administrative law and criminal law to create legal certainty and protection for public officials in carrying out their duties